An equijoin-optimization technique for Malaysian Hydrological Information System (MHIS) data - Kurmin, Norazrin; Selamat, Harihodin; Wahid, Mohd. Taib; Mohd. Rahim, Mohd. Shafry (2005)
Malaysian Hydrological Information System (MHIS) is one of the GIS applications that storing a large amount of data (such as rainfall, water level, evaporation and water quality). In such situation, it is important to ensure that the storage, retrieval and manipulation of these data are efficiently handled. However, the problem in MHIS is inefficient on retrieval data where it takes a long time to retrieve data. MHIS was developed based on cube system concept. The main objective introduced the cube system is to describe how the hydrology data will be store and retrieve in relational database. However, it is still lacking to handle a large amount of data. Thus, this paper proposed an Equijoin Optimization Technique to solve that problem. This technique was introduced based on modification of an equijoin method where an entity will be joined based on equijoin algorithm. In other words, the result relation is a new entity, T, contains tuples t made up of two tuples r and s, where r must be tuple in entity R and s must be tuple in entity S. Then, there are entity will be classified to other entity based on the appropriate attribute. Based on this technique, a SQL statement was created for data retrieval processing which is referring to the optimized entity. There are four main function in that process i) Select ii) Initialize iii) Operation and iv) Output. Also, in this research, testing and comparison analysis has been done between proposed technique, an Equijoin optimization and the previous technique MHIS Cube System. The result of the testing shows that the proposed technique can improve an execution time for query processing, then solve the issue has been discussed on this research.